Markets for Communist Human Capital: Returns to Education and Experience in the Czech Republic and Slovakia - Robert S. Chase (Yale University, Economic Growth Center, 1997)
This research examines differences in earnings structure between Communist and post-Communist Czech Republic and Slovakia using four sets of similar micro-data. It presents hypotheses about how earnings dispersion returns to education and returns to experience will change across regimes and tests those hypotheses using earnings equations. From approximately 2.5 percent in 1984, the return to education increased to approximately 5 percent by 1993. During that period, returns to experience fell. Though women have higher returns to education, returns for men increased more across regime change. Those with academic secondary education experienced a particularly large earnings increase. Earnings structure changes appear larger in the Czech Republic than in Slovakia.
Keywords: 330; Post-Communist Transition; Czech Republic; Slovakia; Returns to Education; Returns to Experience